Strategi Public Relation Dalam Membangun Citra Perusahaan Pada PT Kilang Pertamina Internasional Refinery Unit III Plaju Kota Palembang - Deddy Hendarwan; Yustin Kurniawan (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
The purpose of this study was to analyze the public relations strategy, corporate image and the role of public relations strategy on corporate image at PT Kilang Pertamina Internasional Refinery Unit III Plaju. The research method used is a quantitative approachwith data collection techniques namely, questionnaires, and literature study. The type of research used is explanatory research. A sample of 80 people from the community and Instagram followers of PT Kilang Pertamina Internasional Refinery Unit III Plaju. The sampling technique uses accidental sampling. The results of this study indicate that the public relations strategy has a significant effect on the corporate image of PT Kilang Pertamina Internasional Refinery Unit III Plaju. The results of the analysis, the authors show that the optimization of strategies through the media has no effect on the company PT Kilang Pertamina Internasional Refinery Unit III Plaju. This is evidenced by the results of the t test for indicators of strategy optimization through the media with a t count value of 0.97 which is less than t table 1.664 and a significant value of 0.357 greater than 0.05.